2016
DOI: 10.1038/srep36758
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma VEGF levels following ischemic preconditioning are associated with downregulation of miRNA-762 and miR-3072-5p

Abstract: Ischemic preconditioning (IPC) has protective effects against ischemia-perfusion injury of organs. In the present study, we investigated the associated mechanisms after performing remote IPC (rIPC) of lower limbs by clamping abdominal aorta in mice. Subsequent experiments showed decreased damage and paralysis of lower limbs following spinal cord injury (SCI). Concomitantly, plasma vascular endothelial growth factor (VEGF) levels were increased 24 h after rIPC compared with those in sham-operated animals. In su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 46 publications
(45 reference statements)
1
21
2
Order By: Relevance
“…This further validated the roles of ischemia in promoting DR progression, whereas ischemic postconditioning downregulated retinal VEGF expression in tree shrews that received both STZ administration and cerebral ischemia challenge, indicating the protective roles of PC. Contrary to our experiment results in tree shrews, some studies demonstrated that ischemia or hypoxia conditioning was able to increase VEGF expression [25,26]. Probably, this discrepancy was due to the disease models with different species of animals and different experimental strategies for ischemia or hypoxia conditioning.…”
Section: Discussioncontrasting
confidence: 99%
“…This further validated the roles of ischemia in promoting DR progression, whereas ischemic postconditioning downregulated retinal VEGF expression in tree shrews that received both STZ administration and cerebral ischemia challenge, indicating the protective roles of PC. Contrary to our experiment results in tree shrews, some studies demonstrated that ischemia or hypoxia conditioning was able to increase VEGF expression [25,26]. Probably, this discrepancy was due to the disease models with different species of animals and different experimental strategies for ischemia or hypoxia conditioning.…”
Section: Discussioncontrasting
confidence: 99%
“…An important finding is that miR-762 expression was elevated in the EP group at 6 hours as measured by miRNA microarray analysis and validated by qPCR. MiR-762 was identified in remote ischemic preconditioning (rIPC) in mouse CD34 + bone marrow cells supporting its role along with miR-3072-5p in preconditioning [26]. However, to our best knowledge this is the first experiment demonstrating a possible role of miR-762 in the LPS-induced early preconditioning in the mouse kidney.…”
Section: Mirna Microarray Validationmentioning
confidence: 74%
“…On the other hand, miR-5126 and miR-6538 has been demonstrated responsive to blood-stage malaria infection, while miR-5126 was confirmed down-regulated in macrophage infected with bacteria Brucella [28]. Of note, they were both down-regulated in exosome extracted from plasma after I/R preconditioning in the abdominal aorta [29], which resembles a mild version of I/R injury in the abdominal circulation. These findings support our result that miR-5126 and miR-6538 decreased in response to intestinal I/R injury and may also be associated with the I/R-induced bacterial translocation in the circulation.…”
Section: Discussionmentioning
confidence: 92%